Thermodynamics and adsorption isotherms of copper ions removal from solutions using synthetic zeolite X - Svilović, Sandra, kemičarka; Rušić, Davor; Žanetić, Ratimir (2008)
Summary: The sorptive removal of copper ions from aqueous solutions using zeolite X has been studied by a batch technique. The impact of solute concentration and temperature on the process of sorption were examined. Using obtained experimental values thermodynamic parameters such as: ΔG0, ΔH0 and ΔS0 were calculated. Langmuir, Freundlich, Dubinin-Radushkevich and Sips isotherms were fitted to experimental data, and their goodness-of-fit were compared. The isotherms that take into account some sort of heterogeneity were found to give a better fit to experimental data than Langmuir. An apparent free energy, calculated using Dubinin-Radushkevich isotherm, showed ion-exchange type of spontaneous and endothermic sorption. The results indicated that synthetic zeolite X can be used as an efficient ion-exchange material for the removal of copper ions from wastewaters
Bibliografija: 34 jed.
Sažetak
Keywords: Bakarni ioni -- Vodena otopina -- Uklanjanje -- Zeolit X -- Adsorpcija -- Ionska izmjena -- Termodinamika -- Adsorpcijske izoterme -- Otpadne vode